Coupling of respiratory and sympathetic activities in rats submitted to chronic intermittent hypoxia - Moraes, Davi José de Almeida; Machado, Benedito Honório; Zoccal, Daniel Breseghello [UNESP] (Elsevier B.V., 2014)
The respiratory modulation of sympathetic activity relies on the balance between excitatory and inhibitory inputs from the brainstem respiratory network to presympathetic neurons of the rostral ventrolateral medulla. This central respiratory-sympathetic contributes for the generation of respiratory-related rhythmical oscillations in heart rate and arterial pressure levels, whose functional effects on the blood gas exchange/perfusion and cardiac work remain to be elucidated. Herein, we discuss the experimental evidence describing the potential neural mechanisms underlying the entrainment between respiratory and sympathetic activities at baseline conditions as well as under conditions of metabolic challenges. We also discuss the possible implications of changes in the strength or pattern of the central respiratory-sympathetic coupling in the genesis of sympathetic overactivity and neurogenic hypertension, including that associated with the exposure to chronic intermittent hypoxia.
Keywords: Sympathetic activity; Respiratory pattern; Hypercapnia; Hypoxia; Hypertension